Isoproterenol-Induced Heart Failure Mouse Model Using Osmotic Pump Implantation - Chang, Sunny C. (Methods Mol Biol, 2018)
Isoproterenol is used widely for inducing heart failure in mice. Isoproterenol is a nonselective beta-adrenergic agonist. The acute model mimics stress-induced cardiomyopathy. The chronic model mimics advanced heart failure in humans. In this chapter, we describe a protocol that we used to induce heart failure in 100+ strains of inbred mice. Techniques on surgical pump implantation and echocardiography are described in detail. We also discuss the impact of drug dosage, duration, mortality, age, gender, and strain on cardiac remodeling responses. The success of model creation may be assessed by echocardiogram or molecular markers. This chapter may be relevant to those who are interested in using this heart failure model.